Pengukuran Usability Google Classroom pada Mahasiswa UINSU Menggunakan Metode System Usability Scale (SUS) - Amanda Putri Rizkita; Nadine Octavianta; Habibah Zahra Siregar; Salsabilla Khairus Syifa; M.Khalil Gibran (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
As one of the digital platforms that is widely used in the world of education, Google Classroom needs to be studied in order to support the teaching and learning process optimally. This study was conducted with the aim of evaluating the extent of the feasibility of using Google Classroom among students using the System Usability Scale (SUS) approach. The study used a quantitative design involving 31 students as respondents. Data collection was carried out through the distribution of a SUS questionnaire containing 10 statements with a Likert scale of 1–5. From the results of data processing, a total score of 2,117.5 was obtained with an average SUS score of 68.30. Referring to the SUS interpretation standard, Google Classroom is classified as acceptable with an adequate level of eligibility. These results indicate that the platform is quite capable of supporting the implementation of online learning in universities. However, a number of aspects still need more attention, especially related to ease of navigation, consistency of interface appearance, and clarity of information delivery. In general, Google Classroom can be recommended as a learning aid, although continuous development is still needed to improve the overall user experience.